2023
DOI: 10.1111/dmcn.15536
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with outcomes of severe acute necrotizing encephalopathy: A multicentre experience in Malaysia

Abstract: Acute necrotizing encephalopathy (ANE) in childhood is a rare clinico-radiological syndrome with distinctive bilateral thalamic lesions. The diagnosis is often based on the criteria proposed by Mizuguchi et al. 1 It comprises a spectrum of virus-associated encephalopathy, 2 often but not exclusively associated with influenza infection and a familial and a relapsing form have been reported. The mortality rates are varied, ranging from 0% to 43% and survivors often have severe disabilities. [3][4][5][6][7][8] Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Their use of an active, case-seeking methodology likely bypassed some difficulties in discussing and documenting the FND diagnosis, such as the fear of increasing stigma for the patient or inciting criticism of the clinician. 1 However, other causes of underdiagnosis -utilizing higher diagnostic thresholds for FND, the perception that FND misdiagnoses are penalized, or the outdated belief that FND is a diagnosis of exclusion 1 -may have led clinicians to underreport in the present study. Their ascertainment method required that physicians opt-in to report FND cases.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Their use of an active, case-seeking methodology likely bypassed some difficulties in discussing and documenting the FND diagnosis, such as the fear of increasing stigma for the patient or inciting criticism of the clinician. 1 However, other causes of underdiagnosis -utilizing higher diagnostic thresholds for FND, the perception that FND misdiagnoses are penalized, or the outdated belief that FND is a diagnosis of exclusion 1 -may have led clinicians to underreport in the present study. Their ascertainment method required that physicians opt-in to report FND cases.…”
mentioning
confidence: 83%
“…Received: 12 March 2023 | Accepted: 17 March 2023 DOI: 10.1111/dmcn.The recent publication by Lee et al1 highlighting the high mortality and morbidity of acute necrotizing encephalopathy of childhood (ANEC) has caught our attention, shedding light on this rare but serious neuroinflammatory disorder that occurs in association with influenza and other neurotropic viruses 2. By contrast to European cohorts and the recently published Canadian cohort,3 where 23% (7/20) have dominant missense mutations in RanBP2/Nup358 causing a This commentary is on the case series by Lee et al on pages 1256-1263 of this issue.familial…”
mentioning
confidence: 99%
“…A retrospective multicentre Malaysian study identified 27 children with ANE over a 12 month period with one-third mortality. 25 While there is no consensus as to the optimum treatment strategy, there is emerging evidence that early and multimodal immunotherapy may at least improve mortality. 25 Alongside broad immunomodulatory strategies, the postulated role of excitotoxicity has led to neuroprotective strategies such as therapeutic hypothermia being employed.…”
Section: New Immune-mediated Syndromes: Virus-associated Encephalopat...mentioning
confidence: 99%
“…25 While there is no consensus as to the optimum treatment strategy, there is emerging evidence that early and multimodal immunotherapy may at least improve mortality. 25 Alongside broad immunomodulatory strategies, the postulated role of excitotoxicity has led to neuroprotective strategies such as therapeutic hypothermia being employed. 26 Despite best efforts, the mortality and morbidity associated with virus-associated encephalopathy syndromes, and ANE particularly, remain high, and prevention may be crucial.…”
Section: New Immune-mediated Syndromes: Virus-associated Encephalopat...mentioning
confidence: 99%
See 1 more Smart Citation